ANALISIS PELAKSANAAN PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM PEMBENTUKAN KARAKTER SISWA KELAS 2 TKJ SMK NEGERI 1 TOMA - Emrika Susanti Maduwu (Universitas Nias Raya, 2023)
This research aimed at analyzing the implementation of PPKn learning in the character building of eleventh grade TKJ at SMK Negeri 1 Toma. This research was designed by using qualitative approach. In analyzing the data, researcher used the theory which was proposed by Miles and Huberman, namely: data condensation, data display, and drawing conclusions. In this study, there were two sources of the data, namely primary data and secondary data that were obtained from eleventh grade students of SMK Negeri 1 Toma. The results of this research were found by analyzing the process of implementing learning and through interviews. The implementation of learning carried out by the teacher in class has included character values. It can be seen from the learning process, PPKn is a core subject in instilling student character. Based on the research results that have been found by the researcher, it can be concluded that the implementation of learning process which carried out by teachers at eleventh grade TKJ in SMK Negeri 1 Toma has included character values. The character formation that has been instilled in students is quite good, although it is still not effective due to factors from students who still do not understand character, lack of civics lessons, and lack of self-awareness of these students. To minimize the obstacles that exist in character building, namely giving students an understanding and examples of disciplined character values, as well as fostering awareness in students about the importance of character.